2011
DOI: 10.1016/j.ejphar.2011.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Utilize conjugated melanotropins for the earlier diagnosis and treatment of melanoma

Abstract: Peptides serve as effective drugs and the contrast agents in the clinic today. However the inherent drawbacks of peptide structures can limit their efficacy as drugs. To overcome this we have been developing new methods to create ‘tailor-made’ peptides and peptide mimetics with improved pharmacological and physical properties. In this work we introduce novel peptide and small molecule conjugated molecules for the earlier diagnosis and treatment of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This kinetic advantage can be very useful in detecting cancer vs. non-cancer tissue. This kinetic advantage also should be applicable for in vivo imaging for detection of cancer following cancer treatments [72–75]. …”
Section: Multivalency and The Melanocortin Systemmentioning
confidence: 99%
“…This kinetic advantage can be very useful in detecting cancer vs. non-cancer tissue. This kinetic advantage also should be applicable for in vivo imaging for detection of cancer following cancer treatments [72–75]. …”
Section: Multivalency and The Melanocortin Systemmentioning
confidence: 99%
“…The MC1R is expressed on various cells of the immune system such as cytotoxic T cells and dendritic cells, where it exerts anti-inflammatory and immunomodulatory effects [3,4]. MC1R is overexpressed on most of the melanoma cells, which makes it the identification tag for melanoma imaging and therapy [5,6]. The MC2R is expressed in the adrenal cortex, where it regulates the production of glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%
“…Upon sun exposure, the endogenous agonist α-melanocyte-stimulating hormone (α-MSH) is produced, which activates MC1R on melanocytes to induce melanin production and skin pigmentation . MC1R is found to be highly expressed in 80% of malignant melanomas, and thus has been demonstrated as a selective target for melanoma imaging. Even with nonselective peptide ligands that can also bind to other melanocortin receptor subtypes, the in vivo imaging studies demonstrated high melanoma uptake and low normal organ uptake except for the kidney. , Ever since its development, the cyclized peptide melanotan-II (Ac-Nle-cyclo­[Asp-His-D-Phe-Arg-Trp-Lys]-NH 2 , MT-II) has been widely used as melanocortin receptor agonists due to its strong potency and serum stability . MT-II also serves as a template for further modifications and conjugations to improve its selectivity, oral bioavailability, and to expand its applications (such as melanoma imaging and therapy , ).…”
mentioning
confidence: 99%